Local studies and excursion internships as a component of vocational training of students within the vocational training program «Local Studies and Tourism» - Kashaba, O.; Shcherbyna, І. (Problems of Engineer-Pedagogical Education, 2023)
In the context of contemporary education development, local history studies are to be recognized as a pivotal pedagogical tool in fostering moral, aesthetic, and patriotic education of the youth. It constitutes an integral facet of historical education, spanning across both secondary schools and higher education institutions. Delving into the history of one’s hometown and exploring the daily life of the micro-society propel students beyond the confines of traditional classroom settings, thereby broadening their horizons, expanding their areas of interest, honing their observational skills, and encouraging a thoughtful stance towards societal phenomena. Essentially, local history studies serve to render the abstract tangible, infusing it with figurative and emotional elements that stimulate conscious understanding. Thus, the ongoing enhancement and refinement of methodologies pertaining to historical and regional studies remain a pressing imperative. The article undertakes an analysis of the content of educational internships encompassing local studies and excursions; the internships are aimed at students pursuing the first bachelor's level within the vocational training program titled “Local Studies and Tourism” at Ukrainian Engineering Pedagogics Academy. The prime objective of educational internships is to furnish students with contemporary techniques and frameworks for orchestrating local study excursions, while concurrently nurturing professional aptitudes and competencies. They cultivate students’ inclination to perpetually update their knowledge and to innovatively employ this reservoir of information within educational and vocational contexts. Such internships imply a coherent progression in the educational trajectory, thereby facilitating the gradual augmentation of theoretical insights and practical proficiencies acquired during the study of pedagogical disciplines aligned with the consolidation of theoretical grounding and practical dexterity in organizing and conducting excursions, charting excursion routes, mastering the nuances of diverse excursion types, and embracing a differentiated approach to local history and excursion facilitation. Educational internships encompassing local studies and excursions constitute an integral and nonnegotiable segment of the educational continuum, serving as the subsequent stage of comprehensive practical training for the first bachelor’s level students enrolled in the course “Local Studies and Tourism” within the Department of Local History, Tourism Work, Social and Humanitarian Sciences at Ukrainian Engineering Pedagogics Academy. The overarching purpose of any internship lies in the reinforcement and deepening of theoretical insights acquired by students over a designated period, alongside the acquisition of professional skills and competencies stipulated by the cluster of vocationally oriented disciplines aimed at grooming specialists in the realm of local history and tourism.